The Influence Of EPS, ROE, And NPM On Stock Returns In Food And Beverage Sub-Sector Companies Listed On The Indonesia Stock Exchange - Lintang Dwi Wulandari; Burhanuddin; Hety Budiyanti; Nurman; Annisa Paramaswary Aslam (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
The food and beverage sector is a strategic sector that has a significant contribution to driving Indonesia's economic growth. However, in the 2019–2024 period, this sector experienced pressure due to high food inflation, rising raw material costs, and weakening public purchasing power which affected stock return fluctuations. (2) This condition is the background to this study which aims to examine the effect of Earning Per Share (EPS), Return on Equity (ROE), and Net Profit Margin (NPM) on stock returns in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). (3) This study uses a quantitative approach with a panel data regression analysis method processed using EViews 12 software, with a total sample of 18 companies during the 2019–2024 period. (4) The results of the analysis show that both partially and simultaneously, the EPS, ROE, and NPM variables do not have a significant effect on stock returns. This indicates that profitability performance has not been able to provide a positive signal for investors in assessing the potential for stock returns. (5) Thus, the results of this study do not support Signaling Theory and provide an indication that stock return movements in the food and beverage sub-sector are more influenced by external factors such as food inflation and macroeconomic conditions compared to the company's internal financial performance.